Plunging Airfoil: Reynolds Number and Angle of Attack Effects - Camacho, Emanuel (2020)
Natural flight has always been the source of imagination for the Human being, but reproducing the propulsive systems used by animals is indeed complex. New challenges in today’s society have made biomimetics gain a lot of momentum because of the high performance and versatility these systems possess when subjected to the low Reynolds numbers effects. The main objective of the present work is the computational study of the influence of the number of Reynolds, angle of attack, frequency and amplitude of the oscillatory movement of a NACA0012 airfoil in the aerodynamic performance for a constant angle of attack over time. The thrust and power coefficients are obtained which together are used to calculate the propulsive efficiency. The simulations were performed using ANSYS Fluent with a RANS approach for Reynolds numbers between 8500 and 34000, reduced frequencies between 1 and 5, and Strouhal numbers from 0.1 to 0.4. The influence of the (constant over time) angle of attack was also studied in the range of 0º to 10º. The results indicate optimal operational conditions for the different Reynolds numbers and unprecedented results of the influence of the angle of attack on the aerodynamic coefficients and the propulsive efficiency is widely explored.